The impact of clinical pharmacist-led hypertension screening at the community pharmacy in Türkiye - OKUYAN, BETÜL; SANCAR, MESUT (My University, 2022)
© 2022 Marmara University Press.The aim of this study was to evaluate the impact of clinical pharmacist-led hypertension screening program (including referring high-risk individuals who are not aware of being hypertensive or prehypertensive to the physician) at a community pharmacy in Türkiye. This prospective observational pilot study was conducted in a community pharmacy located in Mersin-Türkiye between October 2017 and April 2018. Blood pressure measurements were performed by the clinical pharmacist at baseline and follow-up. The rate of participants who had high blood pressure measurements (≥140 mmHg for systolic and/or ≥90 mmHg for diastolic) was determined at the baseline by clinical pharmacist. According to the guidelines, participants with high blood pressure were referred directly to the physician by the clinical pharmacist. In the follow-up, the number of patients diagnosed with prehypertension or hypertension and the changes in their measurement of blood pressure were identified between baseline and follow-up. According to findings of clinical pharmacist-led blood pressure measurement, 23 (37.1%) out of 62 participants with high blood pressure were referred to the physician by the clinical pharmacist. In the follow-up, it was determined that 12 patients (52.2%) out of 23 participants were diagnosed with hypertension by a physician and eight patients (34.8%) out of 23 participants had prehypertensive. According to the findings of this pilot study, it was determined a positive impact of the clinical pharmacist-led hypertension screening program for high-risk individuals for hypertension.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); clinical pharmacist; community pharmacy; Hypertension; preventive health; screening